What drives attitude towards telemedicine among families of pediatric patients? A survey. Issue 1 (December 2017) - Russo, Luisa; Campagna, Ilaria; Ferretti, Beatrice; Agricola, Eleonora; Pandolfi, Elisabetta; Carloni, Emanuela; D'Ambrosio, Angelo; Gesualdo, Francesco; Tozzi, Alberto
Abstract Background Telemedicine has been recognized as a way to improve accessibility, quality, and efficiency of care. In view of the introduction of new telemedicine services, we conducted a survey through a self-administered questionnaire among families of children attending the Bambino Gesù Children's Hospital IRCCS, a tertiary care children's hospital located in Rome, Italy. Methods We investigated sociodemographic data, clinical information, technological profile, attitude towards telemedicine, perceived advantages of telemedicine, fears regarding telemedicine, willingness to use a smartphone app providing telemedicine services and willingness to use a televisit service. Through logistic regression, we explored the effect of sociodemographic and clinical variables and technological profile on willingness of using a telemedicine app and a televisit service. Results We enrolled a total of 751 families. Most patients had a high technological profile, 81% had at least one account on a social network. Whatsapp was the most popular messaging service (76%). Seventy-two percent of patients would use an app for telemedicine services and 65% would perform a televisit. Owning a tablet was associated with both outcome variables - respectively: OR 2.216, 95% CI 1.358–3.616 (app) and OR 2.117, 95% CI 1.415–3.168 (televisit). Kind of hospitalization, diagnosis of a chronic disease, disease severity and distance from the health care center were not associated with the outcome variables. Conclusion Families of pediatric patients with different clinical problems are keen to embark in telemedicine programs, independently from severity of disease or chronicity, and of distance from the hospital.